Neoliberal Governmentality, Public Microfinance and Poverty in Bangladesh: Who are the Actual Beneficiaries?. (April 2019) - Chowdhury, Mohammad Shahjahan; Ahmmed, Faisal; Hossain, Md. Ismail
Most of the earlier studies examined the impact of microfinance on poverty reduction. Few studies emphasized on the broader policy framework and implementation process—the actors and factors associated with the process, which are critical to make an impact. This study is an attempt to explore whether public microfinance service reaches to the poorest through qualitative case study evidence. Some quantitative studies argued that non-profit-oriented Microfinance Institutions (MFIs) have greater outreach than profit-oriented MFIs. This study argues that even the non-profit MFIs could not reach to the poorest through adoption of neoliberal governmentality by demonstrating the Bangladesh Rural Development Board (BRDB), a public organization dedicated for poverty reduction in Bangladesh, as a case. The study found that neoliberal policy of market solution of poverty problem provides a financial market for the better off instead of the poor.